PENINGKATAN KETERAMPILAN RENANG GAYA BEBAS MELALUI METODE PENUGASAN PRAKTIK TERSTRUKTUR: STUDI ACTION RESEARCH PADA ANAK PEMULA USIA 10-11 TAHUN - Mochamad Destri Sutisna; Widiastuti Widiastuti; Oman Unju Subandi; Sujarwo Sujarwo; Herman Chaniago; Fajar Vidya Hartono (Jurnal Porkes, 2026)
The low proficiency in freestyle swimming skills among beginner students aged 10–11 years at the Marlin Swimming School Club in Purwakarta Regency is attributed to a conventional, instructor-centered training approach that lacks sufficient progression and variation. This study aims to improve freestyle swimming skills through the application of a structured practice assignment method. The method used was the Kemmis and McTaggart spiral action research model, conducted over 10 sessions (8 intervention sessions) with 20 beginner students. Data collection utilized an observation sheet covering five skill aspects (body position, leg movement, arm movement, breathing, coordination) on a 1–4 scale. The results showed an average score increase from 9.00 to 15.00 (a 66.7% increase). A paired t-test confirmed a statistically significant improvement (t=11.23, df=19, p<0.001). A total of 95% of the students (19 out of 20) met the passing criteria (score ≥12). In conclusion, the structured practice assignment method is effective in improving the freestyle swimming skills of beginner students. Further research with an experimental design and a control group is recommended to generalize the results.